MOLECULAR DOCKING STUDIES OF MAGE INHIBITORS IN THE TREATMENT OF LUNG CANCER - KUMARAN, M.S.; SAGHANA, P.R.KIRESEE; HEMALATHA, SUSEELA THANKACHY; PRASAD, V.S.SAI DURGA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The insilico methods for drug discovery are becoming increasingly powerful and useful. That in combination with increasing computer processor power. Lung cancer is the leading cause of cancer associated deaths Worldwide and has one of the poorest prognoses among all cancer types. A variety of melanoma antigen A (MAGE-A) genes are commonly detected in non-small cell lung cancers. Their biological function is not well characterized but may involve the regulation of apoptosis and cell cycle progression. In this study ligand-based drug design were employed to design novel MAGE inhibitors from Naringi crenulata found in Asia. The MAGE structure model was built in homology modelling based on known receptors of the same family. A phytochemicals of Naringi crenulata are analysed and optimized with the Arguslab to investigate the interactions between the target compounds and the amino acid residues of the Mage protein .All the compound have shown binding pose between from – 6.54 to -15.34.out of five compound 1,2-benzenedicarboxylic acid show best ligand energy -8.15Kcal/mol with 3 hydrogen bond of distance is 2.1,3.0 and 2.3 Key Words: Lung Cancer, Mage Protein, Docking, Modelling, Naringi Crenulata,Argus lab